2003
DOI: 10.1352/0047-6765(2003)41<237:seimsa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Supported Employment in Maryland: Successes and Issues

Abstract: Information was gathered via a mailed questionnaire from approximately 85% of Maryland service providers offering vocational services funded by the Maryland Developmental Disabilities Administration. The weekly earnings of persons placed in supported employment were 3.5 times the earnings of persons employed on the premises of the service provider. Nevertheless, there was strong evidence that substantial improvements are needed, and possible, in supported employment. Among urgently needed improvements are (a) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…How training is provided should be considered in light of the part-time nature of most supported work placements for workers with severe disabilities (Conley, 2003). Due to the part-time basis of many job placements, there is often insufficient time to adequately train workers in relevant work skills while on the job (Flynn, Wacker, Berg, Green, & Hurd, 1991).…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…How training is provided should be considered in light of the part-time nature of most supported work placements for workers with severe disabilities (Conley, 2003). Due to the part-time basis of many job placements, there is often insufficient time to adequately train workers in relevant work skills while on the job (Flynn, Wacker, Berg, Green, & Hurd, 1991).…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…[31][32][33] On average, they work approximately 20 to 28 hours per week. 23,31,34 In SE, the mean hourly wage is usually close to or slightly above the federal minimum wage. 31,34 This is more than twice the hourly wage of individuals working in sheltered workshops, and total earnings exceed those of individuals working in sheltered workshops by 3.5-fold because the individuals in SE tend to work more hours.…”
Section: Employment Outcomesmentioning
confidence: 99%
“…23,31,34 In SE, the mean hourly wage is usually close to or slightly above the federal minimum wage. 31,34 This is more than twice the hourly wage of individuals working in sheltered workshops, and total earnings exceed those of individuals working in sheltered workshops by 3.5-fold because the individuals in SE tend to work more hours. 34 Hall et al 29 reported that only 13% of individuals with an IQ of 50 to 70 who could be located at 42 to 43 years of age were earning more than the population median income.…”
Section: Employment Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of supported employment found that inadequate transportation and employment opportunities, insufficient support, and disincentives for work associated with Supplemental Security Income and Social Security Disability Insurance benefits represented significant barriers to obtaining employment for persons with DD (Conley, 2003). The evidence regarding the extent to which psychiatric disorders and DD represent an obstacle to obtaining supported employment placement is inconclusive.…”
Section: Barriers To Obtaining and Maintaining Employmentmentioning
confidence: 99%